Systemic archetypes for value co-creation based on collaborative cores: Case study at a telecommunication company [Arquetipos Sistémicos para la co-creación de valor con base en núcleos colaborativos: Un estudio de caso en una empresa de telecomunicaciones] (2014)
Currently value creation is not an exclusive aspect of the company; the clients co-creator role has taken preponderance due to the contribution of co-creation models, which demonstrate its utility empirically but does not take into account value construction with a systemic approach. The present work proposes a co-creation model through systemic archetypes that allow the capture of value elements, which arise from the service use experiences. The register of attributes through software is used after the client́s expression of the attributes using a constructive dialogue for which a qualitative focus is adopted in order to find a socially constructed meaning, having as research central axis the interpretative phenomenological analysis. The results show that the methodology allows the value capture through the evaluative speech acts which belong to the language philosophy.